Haemoglobin S and C affect the motion of Maurer's clefts in Plasmodium falciparum‐infected erythrocytes. (20th January 2013) - Kilian, Nicole; Dittmer, Martin; Cyrklaff, Marek; Ouermi, Djeneba; Bisseye, Cyrille; Simpore, Jacques; Frischknecht, Friedrich; Sanchez, Cecilia P.; Lanzer, Michael
Summary The haemoglobinopathies S and C protect carriers from severe Plasmodium falciparum malaria. We have recently shown that haemoglobin S and C interfere with host‐actin remodelling in parasitized erythrocytes and the generation of an actin network that seems to be required for vesicular protein trafficking from the Maurer's clefts (a parasite‐derived intermediary protein secretory organelle) to the erythrocyte surface. Here we show that the actin network exerts skeletal functions by anchoring the Maurer's clefts within the erythrocyte cytoplasm. Using a customized tracking tool to investigate the motion of single Maurer's clefts, we found that a functional actin network restrains Brownian motion of this organelle. Maurer's clefts moved significantly faster in wild‐type erythrocytes treated with the actin depolymerizing agent cytochalasin D and in erythrocytes containing the haemoglobin variants S and C. Our data support the model of an impaired actin network being an underpinning cause of cellular malfunctioning in parasitized erythrocytes containing haemoglobin S or C, and, possibly, for the protective role of these haemoglobin variants against severe malaria.